Pharmalens Augmented Reality Application For The Dangers of Illegal Drugs - A. Muh. Nurul Akbar; Imran Firman (Pusat Penelitian dan Pengabdian Pada Masyarakat Sekolah Tinggi Manajemen Informatika dan Komputer AKBA Makassar, 2024)
The circulation of illegal drugs in Indonesia has escalated significantly in recent years, particularly in the form of tablets and capsules openly sold in various pharmacies. Alarmingly, some of these drugs contain harmful chemicals that pose severe health risks and can lead to fatal consequences if consumed excessively. Field observations reveal a critical gap in public education and awareness regarding illegal drugs, exacerbated by ineffective traditional information dissemination methods such as printed media and direct outreach programs. This study addresses these challenges by leveraging advancements in digital technology to deliver information in an engaging and contemporary manner. An interactive application was developed using the Multimedia Development Life Cycle (MDLC) method, particularly the Luther-Sutopo model, integrating multimedia elements such as images, audio, video, animations, and educational articles. The application employs Augmented Reality (AR) technology, specifically Marker-Based Tracking, to display virtual 3D models triggered by markers or images. The inclusion of voice-over features and informative articles further enhances accessibility and comprehension. Testing results indicate that the AR-based application effectively presents educational content on illegal drugs, facilitating an immersive and impactful learning experience. By fostering greater public awareness and vigilance, this innovative approach contributes to the prevention of illegal drug misuse and supports broader health and safety objectives.